Tinjauan Pendapatan Moda Angkutan Umum Elf Bison Rute Stasiun Wonokromo – Terminal Porong Berdasarkan Demand dan Load Factor - R Endro Wibisono; Muhammad Shofwan Donny Cahyono (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
The city of Surabaya as the capital of East Java, whose transportation system uses public transportation as a means of urban transportation, so that the existence of public passenger transportation is very important and necessary in order to serve passengers optimally. Bison transportation also has a role in meeting the transportation needs of the community. Tariff is an important factor in getting the services and facilities provided. The rate is also adjusted based on the evaluation of vehicle operating costs (BOK). The purpose of this study was to determine how much the tariff for bison vehicles, the matrix of origin from which bison came to the destination, the calculation of the demand for each segment per year, the annual revenue for each segment. The method used in this research is primary data collection in the form of a passenger demand survey, secondary data in the form of a tariff component so that the calculation of vehicle operating costs (BOK) and investment for each segment is analyzed. The result of this research is that the total income per year is IDR 27,895,244. The total fleet is IDR 27,895,244. x 4 fleets to the total revenue of bison public transportation is Rp. 111,580,976 per year.